A case study on savings account-i Syabab (Teenager) in Bank Rakyat / Faza Nurul Ain Mohd Zainol - Mohd Zainol, Faza Nurul Ain (Faculty of Business and Management, 2009)
The electronic banking, since its commercialization, has expanded with tremendous rapidly. This development has been still further assisted by the creation of the World Wide Web, which has caught the imagination of users around the world. Savings account one of the elements electronic banking that offer to customer to spend or withdraw their money from ATM machine. There has variety type of savings account that customer can choose. The purpose of this study about savings account-i Syabab that offer by Bank Rakyat for teenager and will be focuses on Jalan Tangsi branch. The scope of study focuses on Jalan Tangsi branch only and used secondary data as reference. It also uses observation and in-depth interview. The main objective of this study, to know the strategy that Bank Rakyat applied in order to attract the customer and determine the action plan that can be used to promote this account. It shows the long term and short term plan that Bank Rakyat used in order to attract their focus group.